2004
DOI: 10.1007/s00442-004-1653-9
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of cell-mediated immunity in nestling house sparrows

Abstract: Cell-mediated immunity is an important vertebrate defense against pathogens, but components of this response may vary in quality. Such variation could arise through the effects of ecology on optimal immunocompetence. We used injections of phytohaemagglutinin (PHA) to measure the factors influencing T-cell proliferation in nestling house sparrows ( Passer domesticus). Bivariate analyses revealed positive associations with nestling mass and size, but no effect of ectoparasites. The response to PHA was, however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 32 publications
(50 reference statements)
2
16
1
1
Order By: Relevance
“…Moreover, the absence of a significant interaction between sex and condition on the PHA response suggests that the effect of condition on the PHA response does not differ between the sexes. The positive relationship between cutaneous immune response and the condition index is consistent with that reported in most studies of altricial nestlings in a variety of species (e.g., Westneat et al 2004;Moreno et al 2005;Lobato et al 2008; but see Sandell et al 2009). Experimental studies have demonstrated that covariance between the response to PHA injection and condition measures often reflects an underlying direct causal link mediated by access to critical resources.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Moreover, the absence of a significant interaction between sex and condition on the PHA response suggests that the effect of condition on the PHA response does not differ between the sexes. The positive relationship between cutaneous immune response and the condition index is consistent with that reported in most studies of altricial nestlings in a variety of species (e.g., Westneat et al 2004;Moreno et al 2005;Lobato et al 2008; but see Sandell et al 2009). Experimental studies have demonstrated that covariance between the response to PHA injection and condition measures often reflects an underlying direct causal link mediated by access to critical resources.…”
Section: Discussionsupporting
confidence: 81%
“…Similarly, in Eurasian Kestrels (Falco tinnunculus L., 1758), a species in which males are the smaller sex, male nestlings show a weaker immune response than females, but only when food is limited (Fargallo et al 2002). Other studies have also reported an effect, often sex-dependent, of nestling mass, condition, parasite load, or health state on the cutaneous immune response (Tschirren et al 2003;Westneat et al 2004;Chin et al 2005;Palacios et al 2009). …”
Section: Introductionmentioning
confidence: 91%
“…Our data suggest that C. hemapterus rejects nests with abundance of vegetable matter since no flies emerged from these nests despite their probably being nests of bird species reported to be hosts of this parasitic fly (e.g., Sturnus and Passer spp., see Grimaldi, 1997). This agrees with the low prevalence and infestation intensity of C. hemapterus found by Westneat et al (2004) starlings (Sturnus vulgaris). Valera et al (unpubl.…”
Section: Limitation Of Interspecific Competition By Spatial and Temposupporting
confidence: 88%
“…No significant differences appeared in initial body mass between LB (low-begging) and HB (high-begging) nestlings (RM-ANOVA, between-subjects component, Finally, given that the immune response is (directly or indirectly) affected by date, brood size and body mass (Westneat et al 2004), I repeated the models controlling for these variables. For the largest nestlings, the immune response significantly diminished with date, and it remained significantly affected by treatment, so that nestlings begging more fiercely showed a depressed immune response (table 2a).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in the between-subjects component, the test analysed the effect of the treatment on the dependent variables, considering the brood as a statistical unit, thereby avoiding pseudoreplication (von Ende 2001). In a final analysis I used general linear models (GLM), in which I introduced date, brood size and initial nestling body mass as covariates, given that these factors affect (directly or indirectly) the immune response in the house sparrow (Westneat et al 2004). In this last analysis, RM-ANOVA was not possible, and the largest and the smallest nestlings were analysed separately.…”
Section: Methodsmentioning
confidence: 99%